Modeling the kinetics of essential oil content and main constituents of mint (Menthaaquatica L.) leaves during thin‐layer drying process using response surface methodology. Issue 6 (19th April 2021) - Taheri‐Garavand, Amin; Mumivand, Hasan; Fatahi, Soodabeh; Nasiri, Amin; Omid, Mahmoud
Abstract: The purpose of this study was to investigate changes in essential oil content and the main components of mint ( Mentha aquatica L.) during thin‐layer drying process. Response surface methodology (RSM) based on radial basis functions was used to model the relationships between drying temperature and different drying time (independent variables) and essential oil content and main essential oil compounds of mint (dependent variables). Results of gas chromatography with flame ionization detectior (GC‐FID) and gas chromatography‐mass spectrometry (GC‐MS) analyses showed linalyl acetate, 1, 8‐cineol, and linalool are the most abundant constituents of essential oil. Inverse multiquadrics model was the best model to predict the percentage of linalyl acetate, 1, 8‐cineol, and essential oil content, whereas Gaussian model was the best to predict linalool. The efficiency of the selected models was acquired with R 2 of 0.9658, 0.9514, 0.9568, and 0.9828 for essential oil content, linalyl acetate, linalool, and 1, 8‐cineol, respectively. Practical applications: Results suggest that essential oil content M .  aquatica and its main constituents can be scaled‐up by optimizing drying time and temperature. The superior ability of RSM for modeling and monitoring of essential oil content and main components of M .  aquatica during drying process as a rapid, accurate, nondestructive, and online method was also observed.